THE EFFECT OF PROGRESSIVE MUSCLE RELAXATION ON THE REDUCTION OF BLOOD SUGAR LEVELS IN TYPE II DIABETES MELLITUS PATIENTS IN KAJHU VILLAGE, BAITUSSALAM DISTRICT, ACEH BESAR REGENCY - Desreza, Nanda; Safitri, Widya; Riza, Saiful (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2024)
The prevalence of Type 2 Diabetes Mellitus in Indonesia continues to escalate annually, with unhealthy dietary habits and insufficient physical activity identified as contributing factors to the rise in cases. Among the various approaches to mitigate the impact of Diabetes Mellitus, Progressive Muscle Relaxation therapy has emerged as a potential intervention. This study aims to assess blood sugar levels before and after the application of Progressive Muscle Relaxation therapy in patients with Type 2 Diabetes Mellitus in Kajhu Village, Baitussalam District, Aceh Besar, for the year 2023 Utilizing quantitative research methods, the study adopts a quasi-experimental design, specifically a one-group pretest and posttest design, providing treatment to respondents. Purposive sampling, based on predetermined criteria, is employed to select 12 respondents for the study, which is conducted from July 24 to August 6, 2023. The findings reveal a significant effect of Progressive Muscle Relaxation in reducing blood sugar levels in Type II Diabetes Mellitus patients, as evidenced by a p-value of 0.000. The researchers anticipate that the outcomes of this study will contribute to enhancing information, knowledge, and skills among the respondents. These findings may pave the way for further understanding and implementation of Progressive Muscle Relaxation therapy as a valuable adjunct in the management of Type 2 Diabetes Mellitus.